Untangling multiple inequalities: intersectionality, work and globalisation. (1st December 2015) - ,; ,; ,
Abstract : This article begins by outlining the position of women and work in the Global South, highlighting the precarity of their labour market participation. It then argues that the experiences of these women are often examined within a one-dimensional analytical framework and are therefore invisible in the intersectional literature, which tends to take a Western-centric approach. It also contends that existing research fails to consider the particular domestic and cultural circumstances of the women so examined and how their location in these spaces impacts on their experiences of work. It then argues for an examination of women and work in the Global South that takes an intersectional approach that recognises the complexity of their experiences as generated by multi-categorical and multilevel strands of inequality. It goes on to introduce the contributions to this special issue, which explore inequality through an intersectional lens.